The Gut Virome Database Reveals Age-Dependent Patterns of Virome Diversity in the Human Gut - Gregory, Ann C.; Zablocki, Olivier; Zayed, Ahmed A.; Howell, Allison; Bolduc, Benjamin; Sullivan, Matthew B. (Cell host & microbe, 2020)
The gut microbiome profoundly affects human health and disease, and their infecting viruses are likely as important, but often missed because of reference database limitations. Here, we (1) built a human Gut Virome Database (GVD) from 2,697 viral particle or microbial metagenomes from 1,986 individuals representing 16 countries, (2) assess its effectiveness, and (3) report a meta-analysis that reveals age-dependent patterns across healthy Westerners. The GVD contains 33,242 unique viral populations (approximately species-level taxa) and improves average viral detection rates over viral RefSeq and IMG/VR nearly 182-fold and 2.6-fold, respectively. GVD meta-analyses show highly personalized viromes, reveal that inter-study variability from technical artifacts is larger than any “disease” effect at the population level, and document how viral diversity changes from human infancy into senescence. Together, this compact foundational resource, these standardization guidelines, and these meta-analysis findings provide a systematic toolkit to help maximize our understanding of viral roles in health and disease. [Display omitted] •Assembly of 2,697 gut metagenomes from 32 studies exposed 33,242 viral populations•Inter-study analyses reveal strong study biases at the viral population-level•Viral population detection was higher in bulk versus VLP-enriched metagenomes•Gut viral diversity is age-dependent across healthy, Western people At least 32 studies to date have looked at the human gut virome but with limited consistency. Gregory and Zablocki et al. curate and aggregate these data to provide a systematic virome database; use it to assess study biases, global ecological patterns; and show how viromes evolve throughout the human lifespan.